“Red Menace” as an Element of the US Domestic Policy of 1917-1920: Activities of the Bureau of Investigation of the Ministry of Justice - Y. A. Levin; S. O. Buranok (Научный диалог, 2019)
The article is devoted to the formation of the image of the “Red Menace” by the US Department of Justice in the early twentieth century. It is noted that the revolution in Russia in 1917 immediately riveted the attention of the American public and authorities, while the October revolution and the spread of Bolshevism in Russia provoked on the one hand, a negative reaction from the authorities, on the other hand, contributed to the activation of left-wing political forces in the United States. The purpose of the article is to trace how the Department of Justice and, in particular, the Bureau of Investigations (future FBI), which was gaining strength at the time, saw the implications of the Russian revolution for the internal security of the United States and built the image of this revolution as the “Red Menace”. It is shown that the most important events of this period are the so-called “Palmer raids” associated with the power actions of the Ministry of Justice and the Bureau of Investigation against anarchists, socialists and communists in the United States. It is noted that during this period, John Edgar Hoover, one of the main anti-Communists in US history, the future odious director of the FBI and one of the most influential people in the history of this country, began to work in the Ministry and the Bureau. The authors conclude that the “Red Menace” stereotype formed during the period under review will influence the future US policy towards Russia and during the Cold War.